2013
DOI: 10.1586/1744666x.2014.863149
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen’s effects in chronic autoimmune/inflammatory diseases and progression to cancer

Abstract: Endocrine-immune system interactions are the basis for predominance of autoimmune diseases in women with differences between the fertile and the postmenopausal periods. B cell-driven diseases reach the maximum incidence rate in the reproductive years, at least in women under the effects of serum estrogens and their metabolites (endocrine synthesis). On the other hand, the prevalent peripheral synthesis of estrogens, especially in advanced ages (intracrine synthesis), through the action of aromatases, modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…As most of the patients evaluated in this study were of menopausal age, a better ascertaining of the endocrine-immune system interactions and their relation to autoimmune diseases is of evident importance. Interestingly, estrogens after menopause are mainly synthesized and metabolized in peripheral tissues from androgens (usually known to have a protective anti-inflammatory effect) under the action of the aromatase complex [39]. Presence of inflammatory cytokines are usually enhancers of the aromatase activity that can be translated into an accelerated conversion of androgens towards estrogen metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…As most of the patients evaluated in this study were of menopausal age, a better ascertaining of the endocrine-immune system interactions and their relation to autoimmune diseases is of evident importance. Interestingly, estrogens after menopause are mainly synthesized and metabolized in peripheral tissues from androgens (usually known to have a protective anti-inflammatory effect) under the action of the aromatase complex [39]. Presence of inflammatory cytokines are usually enhancers of the aromatase activity that can be translated into an accelerated conversion of androgens towards estrogen metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the role of endocrine system decreases with age. When women become older and the majority of estrogen is made at a peripheral aromatase, the immune and inflammatory responses of men and women become similar (Cutolo et al, 2014). Calcitriol (1,25(OH)2D3) inhibits the expression of aromatase, an enzyme that catalyzes the production of estrogen at the periphery, using androgen under normal conditions (Cutolo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When women become older and the majority of estrogen is made at a peripheral aromatase, the immune and inflammatory responses of men and women become similar (Cutolo et al, 2014). Calcitriol (1,25(OH)2D3) inhibits the expression of aromatase, an enzyme that catalyzes the production of estrogen at the periphery, using androgen under normal conditions (Cutolo et al, 2014). The high prevalence of autoimmune rheumatoid disease in women is due to a decrease in the down regulation of aromatase due to the deficiency of calcitriol (1,25(OH)2D3), leading to an increase in estrogen production in the periphery, which increases the risk and severity of rheumatoid arthritis (Krishnan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For now we will have to stick to old friends such as methotrexate, MMF and cyclophosphamide in early diffuse cutaneous SSc, even though their clinical benefit is modest at best as shown in the ESOS study and expressed in recent guidelines. [1][2][3] Rituximab is increasingly being used based on observational studies in SSc and its proven potency in rheumatoid arthritis, but requires more robust data. Tocilizumab has shown unexpected benefit on lung function in a phase 2 trial, 4 which if confirmed with phase 3 trial could transform the way we manage SSc-ILD.…”
mentioning
confidence: 99%